Comparison of blood gas parameters with hematological and biochemical parameters in critically III intensive care patients connected to mechanical ventilation - Bilge, Ayşegül; Akça, Hatice Şeyma (Acta Medica, 2023)
Objective: The primary aim of this study was to compare blood gas parameters with laboratory parameters in critically ill intensive care patients who were connected to mechanical ventilation. Our secondary aim was to evaluate the effects of blood gas and laboratory parameters on mortality. Materials and Method: Critical patients over the age of 18 who were admitted to intensive care unit from emergency room or clinics and monitored with mechanical ventilation between January 1, 2021, and December 30, 2021, were included in this study. Analyses were done with the R 4.3.1 (R Core Team) program. Statistical significance was defined by p < 0.05. Results: A total of 150 patients were included in this study, and 42.6% of them were male. 62% of the men and 50% of the women in this study died. We studied the trend accuracy of laboratory hemoglobin, hematocrit, sodium, potassium, glucose and blood gas hemoglobin, hematocrit, sodium, potassium, and glucose values using a modified Bland–Altman analysis. When the analyses from the first day were examined, mean bias (LOA g/dl) for hemoglobin was 0.001 (−0.15 to 0.14) and mean bias (LOA mEq/l) for potassium was −0.19 (−0.23 to −0.16). When the third day analyses were examined, mean bias (LOA g/dl) for hemoglobin was 0.29 (−0.05 to 0.63) and mean bias (LOA mEq/l) for potassium was −0.25 (−0.29 to −0.21). Conclusion: Hemoglobin and potassium, which are blood gas parameters, can be used instead of laboratory parameters in clinical decision-making in critically ill intensive care patients on mechanical ventilation.